Particulate emissions and soot characterisation of diesel engine exhaust for steady-state operating condition using dioctyl phthalate blends with diesel. (15th May 2023) - Arora, Priyanka; Verma, Puneet; Lodi, Faisal; Jafari, Mohammad; Zare, Ali; Stevanovic, Svetlana; Bodisco, Timothy A.; Brown, Richard J.; Ristovski, Zoran
Highlights: Soot image analysis was done for DOP blended fuels. Higher particle emissions for DOP fuel blends. Primary particle diameter decreases for DOP fuel blends. DOP fuel blends have compact soot aggregates. Nanostructure of DOP fuel blends have short and curved fringes. Abstract: The study investigates the particulate emission and soot characterisation of particles originating from a six-cylinder common-rail direct injection (CRDI), turbocharged diesel engine. The experiments were conducted using steady-state operating conditions, a constant rpm of 1500 and four different engine loads (25, 50, 75, and 100%). Three different fuels were tested: neat diesel and two dioctyl phthalate (DOP) blends with diesel (DOP10 and DOP20). Particulate emissions were measured using DMS500 and collected on transmission electron microscope (TEM) grids for further analysis of the morphology and nanostructure of the soot structure. The particle number and mass concentrations for neat diesel were found to be lower than DOP fuel blends for all four loads. The primary particle diameter increases with increase in the engine load and decreases with an increase in DOP fuel content in the blend. A compact structure of soot aggregate was observed for DOP fuel blends compared to that of diesel and it increased with an increase in the engine load. Short and curved fringes were observed for DOP fuel blends. Also, an increase in fringe length and a reduction in fringe tortuosity was observed with an increase in engine load. The fringe separation distance results show an opposite trend with respect to fringe length and fringe tortuosity for DOP fuel blends i.e. less inter-planar spacing was observed for DOP fuel blends compared to that of diesel. This would result in an overall decrease in the oxidation reactivity of soot particles.